How many pairs are there?

Find the number of pairs of positive integers ( x , y ) (x,y )

such that x 2 + 3 y x^2+3y and y 2 + 3 x y^2+3x

are both perfect squares.


The answer is 3.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Leonel Castillo
Nov 28, 2018

We may tackle the problem by setting up the following system of equations: x 2 + 3 y = ( x + t ) 2 y 2 + 3 x = ( y + c ) 2 x^2 + 3y = (x+t)^2 \\ y^2 + 3x = (y+c)^2 For some positive integers t , c t,c . The good thing about this setup is that we can actually bound the values at least one of these variables. Suppose that both t , c > 1 t,c > 1 , then t , c 2 t,c \geq 2 and thus x 2 + 3 y ( x + 2 ) 2 3 y 4 x + 4 y 2 + 3 x ( y + 2 ) 2 3 x 4 y + 4 x^2 +3y \geq (x+2)^2 \implies 3y \geq 4x + 4 \\ y^2 + 3x \geq (y+2)^2 \implies 3x \geq 4y + 4 Adding these two inequalities we obtain 3 ( x + y ) 4 ( x + y ) + 8 3(x+y) \geq 4(x+y) + 8 , a clear contradiction. Without loss of generality let's now assume that t = 1 t=1 . We may do this because it is also impossible to have t < 1 t < 1 . This immediately tells us x 2 + 3 y = ( x + 1 ) 2 3 y = 2 x + 1 x^2 + 3y = (x+1)^2 \implies 3y = 2x + 1 . We could now just plug this into the various expressions we have, but I found it useful to clean this up a little bit. The given equation implies that 2 x + 1 0 m o d 3 x 1 m o d 3 x = 3 k + 1 2x + 1 \equiv 0 \mod 3 \implies x \equiv 1 \mod 3 \implies x = 3k + 1 for some non-negative integer k k . This also tells us y = 2 k + 1 y = 2k + 1 .

Because we have the identity x 2 + 3 y = ( x + 1 ) 2 x^2 + 3y = (x+1)^2 , we already know this expression is a perfect square. We can now just focus on figuring out when is y 2 + 3 x y^2 + 3x a perfect square. Substituting for y , x y,x the expressions with k k we find that 4 k 2 + 13 k + 4 4k^2 + 13k + 4 must be a perfect square. Notice that 4 k 2 + 13 k + 4 = ( 2 k + 3 ) 2 + k 5 4k^2 + 13k + 4 = (2k + 3)^2 + k - 5 . If k > 5 k > 5 , then we would have ( 2 k + 3 ) 2 + k 5 ( 2 k + 4 ) 2 k 5 4 k + 7 0 3 k + 12 (2k + 3)^2 + k - 5 \geq (2k + 4)^2 \implies k-5 \geq 4k + 7 \implies 0 \geq 3k + 12 , a contradiction. Thus, we just have to check the values 0 k 5 0 \leq k \leq 5 . Doing this, we find that the polynomial is only a perfect square when k = 0 , 5 k=0,5 . These give the pairs ( 1 , 1 ) , ( 11 , 16 ) , ( 16 , 11 ) (1,1), (11,16), (16,11) .

Thank you, nice solution.

Hana Wehbi - 2 years, 6 months ago

We could proceed this way also : 3y=t^2+2tx, 3x=c^2+2cy. Solving for x, we get x=c(2t^2+3c)/(9-4ct). As x>0, therefore ct<2.25 or ct=1,2 This yields c=1,t=1 or c=1,t=2 or c=2,t=1 The corresponding values of x and y are x=1,y=1 x=11,y=16 and x=16,y=11

A Former Brilliant Member - 2 years, 5 months ago

Log in to reply

Nice solution too.

Hana Wehbi - 2 years, 5 months ago

1 pending report

Vote up reports you agree with

×

Problem Loading...

Note Loading...

Set Loading...